TINGKAT KECEMASAN SISWA KELAS VII SMPN 47 PEKANBARU DALAM MENGIKUTI PEMBELAJARAN PJOK SENAM LANTAI GULING BELAKANG - Amanda, Fauziah Tiara; Vai, Aref; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: This study aims to determine the level of anxiety of class VII students of SMPN 47 Pekanbaru in participating in PJOK learning, especially the material of backward roll floor gymnastics. This study uses a quantitative descriptive method, with the main instrument in the form of a Likert scale questionnaire and supported by interviews and documentation. The subjects of the study were all 31 students of class VII.1 of SMPN 47 Pekanbaru. The results showed that most students experienced anxiety in the moderate category (74.2%), low category (25.8%), and no students experienced anxiety in the high category. In terms of causative factors, psychological factors (such as fear of failure, lack of self-confidence, anxiety) are more dominant than physiological factors (such as heart palpitations or sweaty hands). Specifically, 90.3% of students experienced physiological anxiety in the low category, while 80.6% of students experienced psychological anxiety in the moderate category. This study concludes that the level of anxiety of students in participating in PJOK learning of backward roll floor gymnastics is still within reasonable limits, but still requires attention, especially in creating safe, enjoyable and emotionally supportive learning. Keywords: Anxiety Level, Backward roll floor gymnastics